Producción y comercialización de ayudas técnicas elaboradas por jóvenes con discapacidad leve en taller protegido de la fundación Tierra Nueva en el sur de la ciudad de Quito - Chamorro Samaniego, Washington Ramiro (2011)
The Sheltered Workshop of Tierra Nueva Foundation, created as a concrete proposal to difficult living conditions of people with disabilities by implementing a project for the production and marketing of Technical Aids for low-income South of Quito, changing perspective society, where the current dependence becomes independent, the prevailing inequality equal opportunities, which requires a progressive and profound transformation of the social environment.